The Action Asia adventure travel guide to the Philippines - Houston, Robert (Hong Kong AAP Limited, 1999)
It introduces its readers to the best destinations and locations in the country for a wide range of adventure and eco-tourism activities.
Keywords: Philippines -- Description and travel -- Guidebooks